Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula - Ribera, Carles; Mas, Eva De (Zootaxa, 2015)
Three new troglobiontic species of the spider genus Cybaeodes Simon endemic to caves in the southeastern Iberian Peninsula are described and illustrated: Cybaeodes indalo sp. n. from Almería, C. dosaguas sp. n. from València and C. magnus sp. n. from Alacant. The new species confirm the presence of Cybaeodes on the Iberian Peninsula and its wide distribution throughout the Western Mediterranean including Algeria, Tunisia, Italy, France, Spain and the islands of Sardinia, Sicily and Mallorca. A record of C. liocraninus (Simon), from an Iberian cave was probably based on misidentified specimens of C. magnus sp. n. C. liocraninus is known only from Algeria and should be removed from lists of the Iberian fauna. In addition, the three new species are clear candidates for protection: they have highly restricted ranges and show a high degree of adaptation to the subterranean environment.